The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.kjms.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid improves non‐small cell lung cancer progression by inhibition of mTOR signaling pathway

Abstract: Gambogic acid (GA) has been shown to inhibit cancer cell proliferation, induce apoptosis, and enhance reactive oxygen species accumulation. However, whether GA could improve multidrug resistance through modulating autophagy has never been explored. We demonstrated that the combination of GA and cisplatin (CDDP) resulted in a stronger growth inhibition effect on A549 and NCI-H460 cells using the MTT assay. Furthermore, treatment with GA significantly increased autophagy in these cells. More importantly, GA-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It is reported that GA inhibited the growth of different types of cancer, including lung cancer, colorectal cancer, prostate cancer and breast cancer, hepatocellular carcinoma, multiple myeloma and leukemia. [14][15][16][17][18][19][20] The antitumor mechanism of GA may be related to inducing apoptosis, inhibiting telomerase, blocking NF-kB signaling pathway and enhancing the accumulation of reactive oxygen species. 21 However, the potential role and molecular mechanisms of GA in cervical cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that GA inhibited the growth of different types of cancer, including lung cancer, colorectal cancer, prostate cancer and breast cancer, hepatocellular carcinoma, multiple myeloma and leukemia. [14][15][16][17][18][19][20] The antitumor mechanism of GA may be related to inducing apoptosis, inhibiting telomerase, blocking NF-kB signaling pathway and enhancing the accumulation of reactive oxygen species. 21 However, the potential role and molecular mechanisms of GA in cervical cancer remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that dysfunction in PTEN/PIK3/AKT/mTOR signaling is involved in tumorigenesis 36 . As an important tumor suppressor gene, PTEN negatively regulates PI3K/AKT/mTOR pathway, inhibiting cell growth and proliferation 37 , 38 . The findings in this study suggest that GA attenuates ESCC cell growth presumably through regulating PTEN and PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Gambogic Acid (GA) is a xanthonoid compound derived from Garcinia hanburyi with anti-cancer activity proved in vitro and in vivo [108].…”
Section: Gambogic Acidmentioning
confidence: 99%
“…The effect on cell death could be markedly reduced by the addition of autophagy inhibitors -3-MA and CQ. Moreover, treatment with GA was linked to Akt/mTOR pathway inhibition and the addition of mTOR inhibitor -rapamycin further increased autophagic flux and cell death [108].…”
Section: Gambogic Acidmentioning
confidence: 99%